2010
DOI: 10.1539/joh.l8149
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase‐3 and Vitamin D Receptor Genetic Polymorphisms, and Their Interactions with Occupational Exposure in Lumbar Disc Degeneration

Abstract: Objectives: To investigate the occupational and genetic risk factors inducing lumbar disc degeneration in a Chinese population, and to explore their synergistic interactions. Methods: A case-control study involving 178 low back pain patients with lumbar disc degeneration and 284 controls was carried out. Five types of work-related factors were investigated using questionnaires. Polymerase chain reaction and restriction fragments length polymorphism was used to detect the polymorphisms of MMP-3 (matrix metallop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 25 publications
2
52
1
2
Order By: Relevance
“…In our study, we discerned no association between polymorphisms in MMP-1 and MMP-3 and the age of patients. A previous study investigating the association between disc degeneration caused by occupational trauma and polymorphisms in MMP-3 suggested that the gene-environment interaction could contribute to the development of lumbar disc degeneration in individuals expressing the 5A allele (Yuan et al, 2010). However, we found no association between the various genotypes of MMP-1 and MMP-3 and grades of degeneration in this study.…”
Section: Discussioncontrasting
confidence: 97%
“…In our study, we discerned no association between polymorphisms in MMP-1 and MMP-3 and the age of patients. A previous study investigating the association between disc degeneration caused by occupational trauma and polymorphisms in MMP-3 suggested that the gene-environment interaction could contribute to the development of lumbar disc degeneration in individuals expressing the 5A allele (Yuan et al, 2010). However, we found no association between the various genotypes of MMP-1 and MMP-3 and grades of degeneration in this study.…”
Section: Discussioncontrasting
confidence: 97%
“…Images were reported by a radiologist experienced in musculoskeletal MRI. We used four risk factors agreed by US-NIOSH (USA-National Institute for Occupational Safety and Health), to evaluate the occupational risk factors (Table 1) [12].…”
Section: Methods and Materials/patientsmentioning
confidence: 99%
“…in fact, excessive or inappropriate expression of MMPs may contribute to the pathogenesis of tissue destructive processes in a wide variety of diseases, including various types of cancer, invasion and metastasis of tumor cells, inflammation and degenerative diseases (9)(10)(11)(12)(13)(14). Many studies have investigated the association between polymorphic variants in MMP candidate genes and several diseases.…”
Section: Mmp-3 Polymorphism: Genetic Marker In Pathological Processesmentioning
confidence: 99%